The Role of Marketing and Individual Environment Association in Elevating the Customer Value - Rahayu Kusumadewi (Budapest International Research and Critics University, 2019)
This research aimed at descriptively reviewing marketing and individual environment association upon the customer value as well as verifying the influence of the association upon the customer value, both in partial and simultaneous measurements. A descriptive verification method was applied to the research. Furthermore, the population of the research consisted of students who had been officially registered at Faculty of Teacher Training and Education conducted by Private Universities in West Java Province. A proportional cluster random technique was used to select the sample. In terms of data sources, there were two types: primary and secondary data. To analyze the data, an analysis of Structural Equation Modelling (SEM) was occupied. The result of the research had indicated that marketing and individual environment association and the customer value had shown unsatisfactory outcome. According to verification research, marketing and individual environment association had significantly contributed to the customer value, both in partial and simultaneous measurements.